Comparative analysis of endurance of not hearing and hearing students - Iwańska Dagmara; Madej Anna; Urbanik Czesław (Sciendo, 2013)
Study aim: Sport participation is important for deaf children, as participants experience physical, psychological and social benefits [23]. This study is a summary of four year's researches on the endurance level of deaf and well hearing girls and boys. The aim of this study was to compare endurance of not hearing and hearing students.